A nitrogen source-dependent inducible and repressible gene expression system in the red alga Cyanidioschyzon merolae - Fujiwara, Takayuki; Kanesaki, Yu; Hirooka, Shunsuke; Era, Atsuko; Sumiya, Nobuko; Yoshikawa, Hirofumi; Tanaka, Kan; Miyagishima, Shin-Ya (Frontiers in Plant Science, 2015)
The unicellular red alga Cyanidioschyzon merolae is a model organism for studying the basic biology of photosynthetic organisms. The C. merolae cell is composed of an extremely simple set of organelles. The genome is completely sequenced. Gene targeting and a heat-shock inducible gene expression system has been recently established. However, a conditional gene knockdown system has not been established, which is required for the examination of function of genes that are essential to cell viability and primary mutant defects. In the current study, we first evaluated the expression of a transgene from two chromosomal neutral loci located in the intergenic region between CMD184C and CMD185C, and a region upstream of the URA5.3 gene. There was no significant difference in expression between them and this result suggests that both may be used as neutral loci. We then designed an inducible and repressible gene expression by using promoters of nitrate-assimilation genes. The expression of nitrate-assimilation genes such as NR (nitrate reductase), NIR (nitrite reductase) and NRT (the nitrate/nitrite transporter) are reversibly regulated by their dependence on nitrogen sources. We constructed stable strains in which a cassette containing the NR, NIR or NRT promoter and sfGFP gene was inserted in a region upstream of URA5.3 and examined the efficacy of the promoters. The NR, NIR, and NRT promoters were constitutively activated in the nitrate medium, whereas their activities were extremely low in presence of ammonium. The activation of each promoter was immediately inhibited within a period of 1 hour by the addition of ammonium. Thus, a conditional knockdown system in C. merolae was successfully established. The activity varies among the promoters, and each is selectable according to the expression level of a target gene estimated by RNA-sequencing. This method is applicable to defects in genes of interest in photosynthetic organism.